Special issue on property valuation - Diaz III, Julian; Hansz, J. Andrew (International Journal of Strategic Property Management, 2010)
“Special issue on property valuation”International Journal of Strategic Property Management, 14(1), p. 1First Published Online: 18 Oct 2010